MAINTENANCE OF THE BUTTERFLYFISH Chaetodon striatus (PERCIFOMES: CHAETODONTIDAE) IN A RECIRCULATION SYSTEM - Isabelle Leite Bayona Perez; Ana Paula dos Santos; Bárbara Araújo Martins (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2022)
The hight extractivism of marine fish to supply the demand of the aquarium market has worried the researchers and, in this context,, the aquaculture consists of an alternative to the problem. The family Chaetodontidae represents one of the main families of ornamental marine fish and has not received enough attention on their cultivation research. Considering the absence of this information about the butterflyfish Chaetodon striatus, the present work had the objective of obtaining information about the species in captivity. The fishes were kept in tanks of 100, 200, 300 and 1,000 L, with 6 fishes in each tank, with 3 repetitions for each volume, totaling 72 individuals and were observed for 30 days, being offered living small invertebrates and frozen and fresh mussels for the feeding. Also, for the attempt of reproduction in captivity, two couples, collected directly from the sea, with the entry of only two adults in the trap at a time, were used. Each couple was acclimated in a 100 L tank and we observed their behaviors for 8 hours a day. There was no mortality in tanks of 300 and 1,000 L and, for feeding, small invertebrates and fresh mussels were well accepted. Some behaviors were observed, most of which were already described for chaetodontids. This is the first report of C. striatus in captivity and this contribution may provide subsidies for a future technological package.